Reels de Instagram para el mejoramiento de la comunicación oral en inglés en estudiantes del quinto grado de secundaria en la Institución Educativa Pública 601497 Progreso de San Juan Bautista 2022 - Bosmediano Oliveira, Sary Milagros (2025)
This applicative study was proposed to determine the effectiveness of Instagram Reels as an educational program to enhance oral communication among secondary school students at Public Educational Institution 601497 Progreso in San Juan Bautista, specifically those in the fifth-grade secondary school in 2022. The study followed an evaluative approach with a contemporary field design, cross-sectional, univariable, quasi-experimental. It included a pre – and post – test on oral comprehension and performance as a data collection tools, along with control group. The study consisted of a population and a deterministic sample of 50 students, divided into two groups: experimental (26) and control (24). The final assessment of oral communication revealed that the experimental group outperformed the control group in terms of average score (15.88>9.29). Similarly, the experimental group scored higher in the following dimensions: obtaining oral information (16.79>9.35); inferring and interpreting oral information (16.59>13.30); adapting, organizing, and developing coherent and cohesive ideas (15.00>7.70); use of non-verbal and paraverbal resources (14.54>9.55); strategic oral interaction (14.42>7.04); and evaluation of the form, content, and context of oral discourse (20.00>7.56). In summary, the findings demonstrated that Instagram Reels effectively strengthen oral communication in English among the target population. The research hypothesis was accepted based on the data obtained, with t= 25.440, p-value = 0.00 < α= 0.05 (T-Student, independent samples).